America Policy: Some conceptual thoughts about dealing with the hegemon - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2007)
The starting point of the argument is that America policy should be guided by the plausible assumption that German and European positions are not without influence in the current American debate about the country's role in the world. The fundamental goal of policy towards the United States, consequently, should be to influence this discourse through a two-track approach. While the consensual elements of American leadership (in the sense of liberal hegemony) should be strengthened with words and deeds, levelheaded criticism will remain necessary to counter objectionable elements of American foreign policy that contradict the logic of liberal hegemony and German/European interests and values.In the interest of optimizing influence, such a differentiated America policy will have to consist of a policy mix. According to cost-benefit considerations, three basic strategic options for dealing with individual policy areas can be identified. Firstly, there is the option of closing ranks with United States, whether because the American course coincides with one's own interests, or because in the absence of fundamental divergence of interests participation will give the chance to influence the details of a policy that is largely determined by the United States. The second option is to assert German/European alternatives through "soft balancing". This can involve using international institutions in order to restrict the exercise of American power or at least to gain influence over it. Another form can be the refusal to give international legitimacy to American actions or to particular policy concepts. "Soft balancing" can also involve showing independent international leadership in those fields where the United States tends to block progress rather than initiate it. The third option, finally, is that of conditional cooperation. (SWP Research Papers)
Keywords: 320